Pemanfaatan Labu Kuning dan Rumput Laut dalam Pembuatan Dodol - Rahmayuni, Rahmayuni; Dewi, Yossie K; Selfianti, Dinda (AGRITEKNO: Jurnal Teknologi Pertanian, 2023)
Fruit dodol is a mixture of pumpkin paste, coconut milk, seaweed flour, brown sugar, and glutinous rice flour. Using pumpkin in the manufacture of Dodol, apart from having a high fibre content, can also provide a distinctive taste and aroma in food preparations. Adding seaweed improves the texture of the pumpkin Dodol, so it is chewier. The purpose of this study was to obtain the selected ratio between pumpkin paste and seaweed flour in making dodol according to the quality standard of fruit dodol based on SNI 4297:1996. The treatment in the study consisted of four treatments and four replications and used a Completely Randomized Design. The ratios in the pumpkin paste and seaweed flour, namely 100:0, 80:20, 60:40, and 40:60. The results showed that the LR2 (80% pumpkin paste : 20% seaweed flour) fruit dodol based on SNI NO. 01-4296-1996 met quality standards for fruit dodol with a moisture content of 16.46%, an ash content of 1.07%, a crude fiber content of 3.52%, and a total sugar content of 39.22%. The dodol on the LR2 descriptive sensory assessment of the dodol made by the panelists obtained a very brown color, had the aroma of pumpkin and seaweed, tasted of pumpkin and seaweed, had a chewy texture, and was overall liked by the panelists.